2015
DOI: 10.1016/j.str.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Multi-specificity of MRG Domains

Abstract: Summary Chromatin-binding proteins play vital roles in the assembly and recruitment of multi-subunit complexes harboring effector proteins to specific genomic loci. MRG15, a chromodomain-containing chromatin-binding protein, recruits diverse chromatin-associated complexes that regulate gene transcription, DNA repair, and RNA splicing. Previous studies with Pf1, another chromatin-binding subunit of the Sin3S/Rpd3S histone deacetylase complex, defined the sequence and structural requirements for interactions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 54 publications
6
48
1
1
Order By: Relevance
“…Mrg15 (also known as Eaf3 in yeast) contains an N-terminal chromo domain that has been reported to recognize H3K36me2/3, although the binding affinities of Mrg15 for methylated H3K36me2/3 peptides are fairly low ( K d ≈ 200–400 μM) 31 33 . Mrg15 also contains a C-terminal MRG domain that is mainly responsible for protein–protein interactions 34 37 . Mrg15 and the yeast homolog Eaf3 have been reported to be subunits of two other histone-modifying enzyme complexes: the NuA4 histone acetyltransferase complex 38 41 and the Rpd3S (or Sin3a in higher eukaryotes) histone deacetylase complex 42 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Mrg15 (also known as Eaf3 in yeast) contains an N-terminal chromo domain that has been reported to recognize H3K36me2/3, although the binding affinities of Mrg15 for methylated H3K36me2/3 peptides are fairly low ( K d ≈ 200–400 μM) 31 33 . Mrg15 also contains a C-terminal MRG domain that is mainly responsible for protein–protein interactions 34 37 . Mrg15 and the yeast homolog Eaf3 have been reported to be subunits of two other histone-modifying enzyme complexes: the NuA4 histone acetyltransferase complex 38 41 and the Rpd3S (or Sin3a in higher eukaryotes) histone deacetylase complex 42 46 .…”
Section: Resultsmentioning
confidence: 99%
“…The MRG domains form homodimers and interact with other proteins to form functional complexes (Zhang et al, 2006b; Xie et al, 2015). As a “Royal Family” member, the N-terminal chromodomain functions as a histone reader that specifically recognizes methylated histone markers (Yap and Zhou, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The coupled folding‐binding process is a complex process. The binding target could dictate the folded structure and the folding mechanism of IDPs, which is reflected in binding of different IDPs to a common target and an IDP to different targets . Very recently, N TAIL /XD and N TAIL /hsp70 interactions were comparatively investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The binding target could dictate the folded structure and the folding mechanism of IDPs, which is reflected in binding of different IDPs to a common target and an IDP to different targets. [63][64][65][66] Very recently, N TAIL /XD and N TAIL /hsp70 interactions were comparatively investigated. It was found that N TAIL adopts different conformations upon binding to XD and hsp70, and the binding mechanisms are different.…”
Section: Target Binding Do Not Change the Folding Mechanisms Of Barmentioning
confidence: 99%